Rancang Bangun Model Turbin Pelton Mini Sebagai Media Simulasi/Praktikum Mata Kuliah Konversi Energi Dan Mekanika Fluida - Hadimi, Hadimi; Supandi, Supandi; Rohermanto, Agus (Jurnal Semesta Teknika, 2006)
This Research is conducted in Pontianak state Polytechnic using test-drive method based on literature. The step are scheme/ turbine design, making and repairing in order to get a better pelton turbine. The main objective of this research is to provide facility for energy conversion and fluid mechanism practice which is limited in Mechanical Engineering Department so that it is hoped that it will contribute positive effects on students ability in that field. The construction and specification of pelton turbine model resulted of this research as follows; ( 1) Type Pump: Jet propulsion Pump, with the energy input 500 Watt, head pump 55 m, and debit 30 L / minute. ( 2) Generator energy 500 VA and Rpm 1500 rpm, 50 Hz. ( 3) Runner specification: The sum of buckets / sudu is 8 ( single and double), runner diameter 17 cm, out side diameter 44 cm, the width of bucket 6 cm, the length is 14 cm, and pitch pelton wheel diameter is 30 cm. ( 4) Nozzle diameter is 20 mm. The result of research on this pelton turbine model shows of water kinetic energy into electrical energy resulted by pelton turbine, and the bucket type design as well as the sum influence the rpm and voltage gained.